1992
DOI: 10.1016/s0095-5108(18)30481-0
|View full text |Cite
|
Sign up to set email alerts
|

Nephrocalcinosis

Abstract: The pathogenesis of NC in VLBW infants appears to be multifactorial. The vulnerability of extreme immaturity and the underdevelopment of renal function may be the most important variables. In some ways, we view this problem as similar to that of retinopathy of prematurity. (Clearly the exposure of the retina to high partial pressures of oxygen contributes to the development of retinopathy of prematurity but other variables--some known, such as an immature retina, and others not yet defined--must be present.) H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
3
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 49 publications
3
37
3
1
Order By: Relevance
“…Although the etiological factors leading to NC and nephrolithiasis may be similar, it is unclear which factors favor the occurrence of calcifications in one or the other [2, 3] and some patients may present both NC and nephrolithiasis. However, the frequency of medullary sponge kidney, primary hyperparathyroidism, distal renal tubular acidosis and hyperoxaluria is higher among NC patients [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the etiological factors leading to NC and nephrolithiasis may be similar, it is unclear which factors favor the occurrence of calcifications in one or the other [2, 3] and some patients may present both NC and nephrolithiasis. However, the frequency of medullary sponge kidney, primary hyperparathyroidism, distal renal tubular acidosis and hyperoxaluria is higher among NC patients [4]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that between 20 and 60% of this patient population develops nephrocalcinosis and nephrolithiasis secondary to the treatment with the loop diuretic [3,4,6]. In 1994, Alon et al [7] reported a small series of older infants who developed nephrocalcinosis in association with furosemide treatment for congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…10 Supersaturation of urine with calcium results in intratubular crystal formation at the tip of the renal papilla. 7 Increased urinary calcium excretion is a common complication of vitamin D and oral phosphate therapy, and it is associated with nephrocalcinosis. 3,4 HCTZ decreases urinary calcium excretion both by direct tubular effect and by volume depletion, leading to increased distal tubular sodium and calcium resorption.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 Hypercalcuria also has been shown to be associated with nephrocalcinosis in distal renal tubular acidosis, hyperparathyroidism, prolonged immobilization, Bartter's syndrome, hypophosphatasia, certain tumors, high-dose vitamin D therapy, and idiopathic and drug-induced hypercalcuria. [7][8][9][10][11][12][13] Hydrochlorothiazide (HCTZ) decreases urinary calcium excretion. The effect of HCTZ on nephrocalcinosis in children with XLH is not known.…”
mentioning
confidence: 99%